Comprehensive pre- and in-hospital near-infrared-spectroscopy (NIRS) monitoring after return of spontaneous circulation predicts neurological outcome following out-of-hospital cardiac arrest: a prospective observational study and literature review - Schnaubelt, Sebastian; Kornfehl, Andrea; Eibensteiner, Felix; Schriefl, Christoph; Mayr, Florian B.; Aigner, Patrick; Gatterbauer, Mathias; Girsa, Michael; Grassmann, Daniel; Zajicek, Andreas; Spiel, Alexander; Schreiber, Wolfgang; et al. (Frontiers in Medicine, 2025)
BackgroundAn increase in regional cerebral oxygen saturation (rSO2) levels during advanced life support in patients with out-of-hospital cardiac arrest (OHCA) is associated with return of spontaneous circulation (ROSC) and can predict neurological outcome. Data from the post-ROSC phase are scarce but may predict clinical outcomes as well.MethodsFor this prospective observational study, we measured rSO2 via near-infrared spectroscopy (NIRS) in patients after ROSC following OHCA in both the pre- and in-hospital setting for up to 72 h. Patients were followed up for their post-ROSC treatment and outcomes. NIRS values were then compared between patients with favorable and non-favorable neurological outcomes, and cutoff values were assessed via receiver operating characteristic (ROC) and Classification and Regression Trees (CART) analyses. In addition, a narrative review on the topic was performed.ResultsOf the 27 included patients, 37% survived hospital discharge, and 26% showed favorable neurological outcomes (CPC 1 or 2). RSO2 was significantly higher in individuals with CPC 1/2 (67 [60–69] % vs. 59 [50–70] %; p = 0.049). This was even more pronounced for initial (= a mean of the first 5 min) NIRS values (70 [65–77] % vs. 57 [49–68] %; p = 0.025) and NIRS values rising in the first 10 min (43% vs. 5% of patients; p = 0.042). A ROC analysis for initial rSO2 showed a significant discriminatory power to predict CPC 1/2 (AUC = 0.789, p = 0.025), and both ROC and CART analyses suggested an optimal cutoff of approximately 62% rSO2.ConclusionWe identified a potential RSO2 cutoff measured via NIRS in the post-ROSC phase after OHCA to predict favorable neurological outcomes. Initial values and rising trends may be more useful for prognostication than prolonged ICU measurements. These findings are consistent with previous literature and should prompt both larger clinical trials and consideration of this technology by resuscitation societies.